An Analysis of Students’ Spelling Errors in Writing at the 8th grade of SMPN 2 Kamang Magek - Paramitha, Indah; Syahrul, Syahrul (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The aim of the research was to find out students’ spelling errors and the causes of spelling errors in writing. Writing spelling correctly is important in order to not make misunderstanding for the reader and writer. In field, researcher found some problem at related to students’ spelling errors. Most of students were not interested when they wrote spell correctly. Then, most of students were doubt in the letter that have same sound. The last was most of students often wrote Indonesian spelling in writing English that have similiar sound. The purposes of this research based on three research questions were to find out the kinds of error in spelling, the most common spelling error, and the causes of spelling error were made by students in writing. In this research, the researcher used mix method research by using descriptive design. The mix method was the combination of qualitative research and quantitative research. Quantitative research was used to answer the kind of students’ spelling error in writing and most common of error in writing. Qualitative research was used to know the causes of students’ spelling error in writing. The informants of this research was the students of VIII-1 class in SMP N 2 Kamang Magek. The total was 22 students. The data was got through documentation and interview. Documentation was used to get quantitative data and interview was used to get qualitative data. The researcher asked the students’ writing to the teacher as a documentation. The interview was done directly and indirectly because of the pandemi. The result of the research showed that there were 184 spelling errors from 22 students. There were nine kinds of spelling error such as omission of letter, addition of letter, single letter instead of double letter, double letter instead of single letter, substitution of letter, interchange of two adjacent of letter, involving an apostrophe, multiple error. Therefore, the most common spelling error was substitution of letter which students changed letter incorrectly with 35,3% percentage. Moreover, there were some reasons why the students of SMP N 2 Kamang Magek made spelling error. The first was the difficulties between spoken and written form in English, it made students were not able to remember the spelling. Second was most of students were influenced by students’ first language when they wrote spelling. The last was lack of students’ desire to write correct spelling.